In vitro and in vivo anti-malarial activity of novel harmine-analog heat shock protein 90 inhibitors: a possible partner for artemisinin. (December 2016) - Bayih, Abebe; Folefoc, Asongna; Mohon, Abu; Eagon, Scott; Anderson, Marc; Pillai, Dylan
Abstract Background The emergence of artemisinin-resistantPlasmodium falciparum strains poses a serious challenge to the control of malaria. This necessitates the development of new anti-malarial drugs. Previous studies have shown that the natural beta-carboline alkaloid harmine is a promising anti-malarial agent targeting theP. falciparum heat-shock protein 90 (PfHsp90). The aim of this study was to test the anti-malarial activity of harmine analogues. Methods Forty-two harmine analogues were synthesized and the binding of these analogues toP. falciparum heat shock protein 90 was investigated. The in vitro anti-malarial activity of two of the analogues, 17A and 21A, was evaluated using a 72-h growth inhibition assay. The in vivo anti-malarial activity was tested inPlasmodium berghei infection of BALB/c mice. The potential of 21A for a combination treatment with artemisinin was evaluated using in vivo combination study with dihydro-artemisinin in BALB/c mice. Cytotoxicity of the harmine analogues was tested in vitro using HepG2 and HeLa cell lines. Results 17A and 21A bound to PfHsp90 with average IC50 values of 12.2 ± 2.3 and 23.1 ± 8.8 µM, respectively. They also inhibited theP. falciparum W2 strain with average IC50 values of 4.2 ± 1.3 and 5.7 ± 1.7 µM, respectively. In vivo, three daily injections ofP. berghei -infected BALB/c mice with 100 mg/kg of either 17A or 21A showed significant reduction in parasitaemia with a 51.5 and 56.1% reduction, respectively. Mice treated with 17A and 21A showed a median survival time of 11 and 14 days, respectively, while the vehicle control mice survived a median of only 8.5 days. A dose-ranging experiment with 21A showed that the compound has a dose-dependent anti-malarial effect. Furthermore, treatment of infected mice with a combination of 21A and dihydroartemisinin (DHA) showed a dramatic reduction in parasitaemia compared to treatment with DHA alone. Conclusion A novel and non-toxic harmine analogue has been synthesized which binds to PfHsp90 protein, inhibitsP. falciparum in vitro at micromolar concentration, reduces parasitaemia and prolongs survival ofP. berghei -infected mice with an additive anti-malarial effect when combined with DHA.